ROLE PLAYS IN EFL CLASSES ON BALANCING TEACHER TALK TIME AND STUDENT TALK TIME (Journal of Universal Science Research, 2023)
The paper states the essence of using role-play in teaching foreign language; the impact on students’ talk; balance of teacher talk time, the role of the listener and speaker. Teachers’ and students’ roles, factors and categories of role-playing are justified in accordance with the linguists’ viewpoints and research.